Independent Curriculum In Improving The Quality Of Education - Putri Anggini; Husna Husna; Naila Faizah S Rambe; Azwa Khalisa Nasution; Inayah Hanum Lubis; Safinatul Hasanah Harahap (Pusdikra-Publishing.com, 2024)
ABSTRACT Education is an important element in building a developed and prosperous nation. The quality of education is the main key in producing the next generation who are superior and able to compete in the era of globalization. The curriculum as the spirit of education plays a crucial role in determining the direction and goals of learning. The Merdeka Curriculum is present as a new breakthrough in the Indonesian education system, with a focus on developing student character and competency that is more flexible and student-centered. The Merdeka Curriculum has become the main focus in discussing the quality of education in Indonesia. This article discusses the role and impact of implementing the Independent Curriculum in improving the quality of education. With a more flexible and competency-based approach, the Merdeka Curriculum aims to strengthen students' skills according to the needs of the times. An in-depth analysis was carried out to evaluate the extent to which the Merdeka Curriculum has succeeded in stimulating student creativity, innovation and independent learning. The research results show that the Merdeka Curriculum encourages the creation of a more dynamic and inclusive learning environment. Keywords: Independent Curriculum, Improving the Quality of Education.